2008
DOI: 10.1128/jb.01870-07
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Genes Repress Motility in Uropathogenic Escherichia coli Constitutively Expressing Type 1 Fimbriae

Abstract: Two surface organelles of uropathogenic Escherichia coli (UPEC), flagella and type 1 fimbriae, are critical for colonization of the urinary tract but mediate opposite actions. Flagella propel bacteria through urine and along mucus layers, while type 1 fimbriae allow bacteria to adhere to specific receptors present on uroepithelial cells. Constitutive expression of type 1 fimbriae leads to repression of motility and chemotaxis in UPEC strain CFT073, suggesting that UPEC may coordinately regulate motility and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 63 publications
3
79
0
Order By: Relevance
“…Constitutive expression of type 1 fimbriae, an essential virulence factor in UTIs (Connell et al, 1996), has been shown to decrease motility of UPEC (Bryan et al, 2006;Lane et al, 2007a), partially due to the abundance of fimbrial structures at the cell surface (Lane et al, 2007a). Subsequent screening of factors that participate in a decreased-motility phenotype identified four transcriptional regulators, LrhA, Lrp, SlyA and P fimbriae protein PapX, that partially restore motility without affecting type 1 fimbriae expression (Simms & Mobley, 2008a). PapX binds to a 29 bp DNA region located 410 bp upstream of the flhD start codon, and when overexpressed, PapX decreases motility of the UPEC strain CFT073 by repressing flhDC transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Constitutive expression of type 1 fimbriae, an essential virulence factor in UTIs (Connell et al, 1996), has been shown to decrease motility of UPEC (Bryan et al, 2006;Lane et al, 2007a), partially due to the abundance of fimbrial structures at the cell surface (Lane et al, 2007a). Subsequent screening of factors that participate in a decreased-motility phenotype identified four transcriptional regulators, LrhA, Lrp, SlyA and P fimbriae protein PapX, that partially restore motility without affecting type 1 fimbriae expression (Simms & Mobley, 2008a). PapX binds to a 29 bp DNA region located 410 bp upstream of the flhD start codon, and when overexpressed, PapX decreases motility of the UPEC strain CFT073 by repressing flhDC transcription.…”
Section: Discussionmentioning
confidence: 99%
“…A phage transductant of the original tosR deletion mutation (10) was unmarked using the FLP recombinase as previously described (10). The ⌬hns ⌬lrp CFT073 strain was engineered through phage-mediated transduction of a previous CFT073 ⌬lrp mutation (19) into a previous lambda Red-engineered CFT073 ⌬hns mutant unmarked as described above. Transductants were selected for on lysogeny broth (LB) agar (10 g/liter tryptone, 5 g/liter yeast extract, 0.5 g/liter NaCl, 15 g/liter agar) containing kanamycin (25 g/ml).…”
Section: Methodsmentioning
confidence: 99%
“…The tos operon, in addition to tosA and predicted cognate secretion system genes tosCBD, also contains the regulatory genes tosR, tosE, and tosF (9,10). TosE and TosF together suppress motility (10), a feature also found in other adhesin operon regulators (19)(20)(21). TosR, a member of the PapB family, is a negative regulator of the tos operon (10).…”
mentioning
confidence: 99%
“…Flagella have been proposed to provide a selective advantage in the early colonization of the urinary tract [33] and flagellum-driven motility is proposed to enhance bacterial dissemination to the upper urinary tract and facilitate bacterial spread to sites more advantageous for colonization [76]. Sp10 was a 100% motile re-isolate, whereas R15-2 contained a mixture of motile and non-motile cells.…”
Section: The Presence Of a Combined Virulence Profilementioning
confidence: 99%